1986
DOI: 10.1083/jcb.102.2.619
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end annealing of microtubules in vitro.

Abstract: Abstract. Mixtures of pre-formed microtubules, polymerized from chicken erythrocyte and brain tubulin, rapidly anneal end-to-end in vitro in standard microtubule assembly buffer. The erythrocyte tubulin segments in annealed heteropolymers can be distinguished by an immunoelectron microscopic assay that uses an antibody specific for chicken erythrocyte betatubulin. An annealing process is consistent with the following observations: (a) Microtubule number decreases while the polymer mass remains constant. (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
2

Year Published

1987
1987
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 32 publications
7
66
2
Order By: Relevance
“…In the case of microtubules, for example, we observed that imperfections in the microtubule wall at the site of joining quickly become filled in or repaired, suggesting a possible requirement for the rearrangement of monomers in the polymer wall or the incorporation of exogenous tubulin monomers (Rothwell et al, 1986). However, our experiments showed that filament annealing was not affected in an obvious way by the addition of actin monomers, even at relatively high molar ratios of monomers to filament ends.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In the case of microtubules, for example, we observed that imperfections in the microtubule wall at the site of joining quickly become filled in or repaired, suggesting a possible requirement for the rearrangement of monomers in the polymer wall or the incorporation of exogenous tubulin monomers (Rothwell et al, 1986). However, our experiments showed that filament annealing was not affected in an obvious way by the addition of actin monomers, even at relatively high molar ratios of monomers to filament ends.…”
Section: Discussioncontrasting
confidence: 43%
“…While monomer exchange at polymer ends is clearly an important factor in determining the growth and stability of polymers of actin and tubulin, it is likely that polymer fragmentation and annealing are also involved in determining the lengths and numbers of polymers at steady state. In recent studies of microtubule assembly, we demonstrated that microtubule polymers can rapidly join end-to-end (anneal) (Rothwell et al, 1986) and that, under certain conditions, mechanisms of polymer annealing and monomer exchange both play important roles in determining microtubule dynamics in vitro (Rothwell et al, 1987). In the present paper, we examine the role of annealing in the assembly of actin filaments.…”
mentioning
confidence: 99%
“…2), the most likely explanation for polymer length redistribution is that many short microtubules annealed end-to-end to form fewer but longer microtubules. Endwise annealing of animal microtubules in vitro was described previously by Rothwell et al (1986). Further evidence for tobacco microtubule annealing was seen in the form of structural discontinuities along polymer walls, where the ends of different microtubules appeared to have joined.…”
Section: Discussionmentioning
confidence: 83%
“…Because a low APM concentration produced fewer but significantly longer microtubules without a large reduction in total polymer mass ( Fig. 2; Table I), long microtubules probably arose from an end-to-end annealing of short microtubules, a phenomenon described previously with animal microtubules in vitro (Rothwell et al, 1986). Apparently, annealing of tobacco microtubules occurred as a result of an APM-induced enhancement of dynamics at microtubule ends.…”
Section: Depolymerization Of Taxol-stabilized Tobacco Microtubules Bymentioning
confidence: 88%
“…The above reasoning yielded a value for the tubulin association rate constant in the elongation (Walker et al, 1988;Simon et al, 1992) and in vivo (Sammak and Borisy, 1988;Shelden and Wadsworth, 1993) but was rare in interphase newt cells (Cassimeris et al, 1988) and in interphase sea urchin egg cytoplasmic extracts (Gliksman et al, 1992). Our simulation also neglected MT annealing (Rothwell et al, 1986), MT severing (Vale, 1991), nonnucleated MT self-assembly, and any minus-end polymerization or depolymerization (Mitchison, 1989;Sawin and Mitchison, 1991;Mitchison and Salmon, 1992) at the nucleation sites. Given our current state of knowledge about MT assembly in the cell, nucleation, and plus-end dynamic instability appear to be the dominate factors in regulating changes in MT assembly in the cell cycle.…”
Section: Kinetics Of Conversion Between Interphase and Mitotic Assemblymentioning
confidence: 99%